Rejoinder to Scott Williams on the Logic of “Through” - Nemes, Steven (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2026)
I have recently argued that the Nicene doctrine of the consubstantiality of Father and Son is incompatible with the assertion that the Father created the world “through” the Son (cf. John 1:3; 1 Cor. 8:6; Col. 1:16–17; Heb. 1:2, 10). Scott Williams has critiqued my essay on two grounds: that its argument is circular and that it does not interact with the exegesis of historic pro-Nicene theologians. This essay proposes a rejoinder to Williams. It argues that his accusation of circularity is uncompelling and that historic pro-Nicene exegesis on this matter is unconvincing